Design and flight testing of the ducted-fan UAV flight array system - Kim, Taegyun; Jeaong, Hoijo; Kim, Seongyoung; Kim, Inrae; Kim, Seungkeun; Suk, Jinyoung; Shin, Hyo-Sang (Springer, 2023)
This study proposes a ducted-fan flight array (DFA) system that can change the array based on the mission environment and validate the feasibility through ground and flight tests. This DFA can carry out normal formation flight as separated UAV members and can also cooperate as a single entity by physical connection. The ducted-fan unmanned aerial vehicle (UAV) is manufactured in-house and equipped with a connected surface and an assembly device on the side to perform connection and separation tasks. Moreover, the control system was designed using an open-source autopilot environment, and the communication environment for multi-UAV flight was constructed using the Robot Operating System (ROS). Then, ground and preliminary experimental tests verified the feasibility and performance of the DFA system for connected and separated flight.
Keywords: ducted-fan flight array system; unmanned aerial vehicle; formation flight; flight test